Enzyme histochemical study of fat absorption in human duodenal mucosa. Issue 10 (October 1974) - Monges, H.; Chamlian, A.; Cougard, A.; Mathieu, B.
Abstract : In seven healthy subjects the activities of various intestinal enzymes were studied using a fasting control peroral biopsy and two other biopsies 15 minutes and 30 minutes after an intestinal infusion of emulsified corn oil. Specific histochemical methods permitted the comparison of the enzymatic activities of the absorptive cells at the top of the villi before and during fat absorption which was demonstrated with a Sudan black stain. Four oxydative enzymes were modified after the corn oil infusion: NADH2-tetrazolium reductase, NADPH2-tetrazolium reductase, glucose-6-phosphate dehydrogenase, and lactate dehydrogenase. In six cases, the activity of NADH2-tetrazolium reductase was increased. Two of these subjects presented a simultaneous increase of NADPH2-tetrazolium reductase and glucose-6-phosphate dehydrogenase. Two other subjects presented a decrease in lactate dehydrogenase activity.